SEDIMENTASI SEBAGAI DILEMA PENGEMBANGAN PELABUHAN NUSANTARA DI PERAIRAN LASEM JAWA TENGAH - Ilhaude, Delyuzar; Usman, Ediar (Jurnal Geologi dan Sumberdaya Mineral, 2007)
The studied area is geographically located on the northern coast of Jawa, which is an open beach influenced by wave action from the northwest and northeast direction. The erosion process occurs relatively in the northeastern coastline of the Lasem area. Sediment supply from the northeastern of Lasem tends to be deposited in the central and the southwestern part of the studied area. The thickness of sediment of subsequence B4 on line L-1 in the southwestern part of the studied area is thicker compared with subsequense B4 on the line L-17 of the northeastern part of the studied area. The eastern part of Lasem can be developed as a harbor area. Keywords : bearing capacity, sediment supply